Perancangan E-Kalfisika Dalam Pembelajaran Fisika Secara Digital - Rizky Eka Adinagoro; Reza Aditya Angga Putra; Rahadian Bintang P; Rio Sandi Laksono; Rudi Susanto (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
Physics is a science with many similarities in each subject. This research on physics calculations aims to create a simple physics calculator based on Python programming. The purpose of this research is to create an electronic physics calculator (e-KalFisika). E-KalFisika is an application used for digital or electronic physics learning. This application provides learning materials, experimental simulations, practice problems and other features that support the understanding of physics concepts. The e-KalFisika application is only in development to solve the problem of calculating physics formulas. The result is e-KalFisika with better calculation results than manually.